Of rodents and foxes: faunal activity and scavenging at carcasses in a Central European (Swiss) forest - Indra, Lara; Moser, Valentin; Milella, Marco; Errickson, David; Lösch, Sandra (Wiley, 2025)
Vertebrate activity can significantly affect forensic investigations. Trauma interpretation is impaired when vertebrates scavenge on injuries and inflict damage, and scavengers can hinder the recovery of human remains through dispersal. However, forensic scavenging research is scarce in Europe and lacking for Switzerland. We conducted a 2‐month baseline study followed by a 5‐month experiment with six domestic pig (Sus scrofa domesticus) carcasses in a Swiss forest during summer through fall. We monitored each three caged and uncaged carcasses with camera traps and documented vertebrate activities and taphonomic signatures on the remains and calculated the scavenging rate. Rodents (Apodemus sylvaticus, A. flavicollis, and Myodes glareolus) and red fox (Vulpes vulpes) scavenged and dispersed the remains. All carcasses and ca. 4% of the recovered bones exhibited scavenging marks, including wet bone scavenging (rodents) mainly on small bones and protruding features, and scoring (red fox) on a rib. The presence of a carcass, decomposition stage, sun exposure, and use of cages significantly influenced the number of vertebrate visits at the plots. Rodents preferentially scavenged caged, skeletonized remains at tree‐covered plots and modified perimortem wounds beyond recognition. The few carnivore sightings focused on uncaged specimens. The generally low scavenger participation was likely season‐related, due to the rapid maggot infestation, or human presence. Future studies should evaluate the influence of these variables, including sun exposure. Our study informs forensic casework by highlighting the importance of rodents and to a lesser degree foxes as vertebrate scavengers and dispersal agents in central European temperate forests.
Keywords: dispersal; forensic anthropology; red fox (Vulpes vulpes); rodents; scavenging; taphonomy; 4402 Criminology; 44 Human Society; 15 Life on Land; Legal & Forensic Medicine